Integrating Data Sources in a Software Project Risk Assessment Model - Radliński, Łukasz (Integracja źródeł danych w modelu do szacowania ryzyka przedsięwzięcia informatycznego, 2010)
This paper discusses integrated software project risk assessment model called the Productivity Model. There are two levels of integration involved with the model: (1) integrating effort, functionality and quality estimation and enabling trade-off analysis between these key project variables; (2) integrated knowledge base used to build the model made of various independent sources: expert knowledge, questionnaire survey results, results from statistical analysis of empirical data, and other reported data. Since the benefits of the first level of integration have been previously discussed this paper focuses on the second level by discussing the process of developing the Productivity Model using different data sources. Although this model reflects the software engineering area, such approach can be followed in building predictive models also in other fields.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 103-113
Keywords: data integration; expert knowledge; risk assessment; project management; Bayesian net